2014
DOI: 10.1111/joie.12056
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graduated Response Anti‐Piracy Laws on Music Sales: Evidence from an Event Study in France

Abstract: Digital piracy is seen as a significant problem for the creative industries. Still, while there have been many academic studies showing that piracy hurts sales, there have been far fewer studies analyzing the effectiveness of anti-piracy measures in reversing this effect. This study attempts to address this question by analyzing how the HADOPI "three strikes" law in France affected digital music sales on the iTunes music store.To do this, we obtained a panel of iTunes sales data from the four major music label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(31 citation statements)
references
References 19 publications
0
29
2
Order By: Relevance
“…Despite these challenges, a few recent studies have examined the effect of specific antipiracy actions on the behavior of a particular group of users (i.e.consumers) in a single country using measurement [1], or survey of users [2] or businesses [3]. All these studies presented a collection of evidences to illustrate that the enforcement of local antipiracy laws succeeded in reducing the downloading activity of copyrighted content among their target group of consumers.…”
Section: Whether and To What Extent An Antipiracy Law And Its Associamentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these challenges, a few recent studies have examined the effect of specific antipiracy actions on the behavior of a particular group of users (i.e.consumers) in a single country using measurement [1], or survey of users [2] or businesses [3]. All these studies presented a collection of evidences to illustrate that the enforcement of local antipiracy laws succeeded in reducing the downloading activity of copyrighted content among their target group of consumers.…”
Section: Whether and To What Extent An Antipiracy Law And Its Associamentioning
confidence: 99%
“…In particular, 72% of the respondents to this survey who had received a warning, declared that they had decreased or stopped their activity, and 50% of the respondent indicated that they have increased the consumption of legal copyrighted content. The second study [3] analyzed the data from iTunes record sales by four major labels and reported 25% increase in the purchase of iTunes music among French users after the enforcement of the Hadopi law while the increase in a neighbor country such as Spain was negligible. Based on these two pieces of evidence, they concluded that the Hadopi law has been successful in deterring P2P downloads of copyrighted material.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Anything in real life, the occurrence and development are all real, there are some things that cause and effect is a kind of inevitable. But in the music creation, imagine whether can get rid of the shackles of reality and authenticity, it can get rid of reality to an "ideal" virtual space.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud computing is known as primary global most anticipated technology revolution, and the cloud is widespread worldwide attention, because it marks, not just a new technology, or caused by technology of the industry of a transformation, will determine the competitiveness of the country. Music cloud or music cloud is not a question of concept that has become the industry investment hot spots [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%